Polarized IR reflectance spectroscopy methods for the orientation of monoclinic single crystals: Tutton salts as a case example - Ivanovski, Vladimir (Society of Chemists and Technologists of Macedonia, 2014)
Investigation of polarized IR reflectance spectra of single crystals is important in the course of obtaining vibrational, optical and dielectric properties of solid state samples.  Diffraction X-ray methods are usually employed for crystal orientation. In this work, two IR reflectance methods are proposed as a supplement in testing the orientation of the b crystal axis and by that the ac crystal plane, in respect to the morphology of monoclinic single crystals. The methods were tested on two Tutton salt single crystals: K2Ni(SO4)2·6H2O and K2Ni(SeO4)2·6H2O and were further compared with the cross-polarization IR reflectance method. Both methods rely on the symmetry and optical properties of monoclinic single crystals. One of them takes into account the fact that one of the principal axes of the dielectric tensor is symmetry fixed, while the other employs the conditions for the appearance of an isosbestic-like point i.e. isosbestic-like region in the polarized IR reflectance spectra of single crystals with low symmetry.